2015
DOI: 10.1001/jama.2015.5161
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Thyroid Dysfunction and Fracture Risk

Abstract: IMPORTANCE-Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE-To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION-The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION-Individual participant data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 302 publications
(212 citation statements)
references
References 59 publications
(85 reference statements)
6
191
0
15
Order By: Relevance
“…5,6,[16][17][18] Even the subclinical form of hypothyroidism and hyperthyroidism are associated with poor bone quality. TSH even moderately below or above the reference range is an independent predictive factor for vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,[16][17][18] Even the subclinical form of hypothyroidism and hyperthyroidism are associated with poor bone quality. TSH even moderately below or above the reference range is an independent predictive factor for vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a meta-analysis by Wirth et al (85) reported a 2.2 higher risk for hip fractures and a 1.4 higher risk for non-vertebral fractures in subclinical thyrotoxicosis. In 2015, a meta-analysis comprising more than 70 000 participants revealed a 3.57 (1.88-6.78) higher risk for spine fractures among subjects with serum TSH lower than 0.10 U/L (86). Sensitivity analyses of the latter study showed a 1.79 (1.04-3.09) higher risk for spine fractures in endogenous thyrotoxicosis.…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…A very recent meta-analysis, including IPD from 13 prospective cohorts, confirmed that Endo SHyper is associated with an increased risk of fractures with an HR of 1.52 (95% CI: 1.19-1.93) for hip fracture, 1.42 (95% CI: 1.16-1.74) for any fracture and 1.74 (95% CI: 1.01-2.99) for spine fracture [109]. Grade 2 SHyper was associated with higher fracture rates with an HR of 1.61 (95% CI: 1.21-2.15; 47 events in 510 participants) for hip fracture, 1.98 (95% CI: 1.41-2.78; 44 events in 212 participants) for any fracture, 1.61 (95% CI: 0.96-2.71; 32 events in 185 participants) for non-spine fracture and 3.57 (95% CI: 1.88-6.78; 8 events in 162 participants) for spine fracture [109].…”
Section: Risks Associated With Persistent and Untreated Endo Subclinimentioning
confidence: 99%